Molecular Insights Into Neutrophil Biology From the Zebrafish Perspective: Lessons From CD18 Deficiency - Bader, Almke; Gao, Jincheng; Rivière, Thibaud; Schmid, Bettina; Walzog, Barbara; Maier-Begandt, Daniela (Frontiers in Immunology, 2021)
Neutrophils are key players in innate immunity and originate from the bone marrow of the adult mammalian organism. In mammals, mature neutrophils are released from the bone marrow into the peripheral blood where they circulate until their recruitment to the site of inflammation in a multistep adhesion cascade. Here, adhesion molecules of the 2 integrin family (CD11/CD18) are critical for neutrophil adhesion to and migration on the inflamed endothelium allowing their extravasation into the inflamed tissue. This is in sharp contrast to neutrophil recruitment in zebrafish larvae (Danio rerio) where neutrophils originate from the caudal hematopoietic tissue and mainly migrate interstitially to the site of lesion upon the early onset of inflammation. In mammals, 2 integrins are dispensable for interstitial migration but critically involved in wound healing. The functional impact of 2 integrins for these processes in zebrafish is completely unknown. Nevertheless, zebrafish larvae are a widely accepted model system to analyze neutrophil trafficking and wound healing in vivo. In this study, we generated zebrafish with a genetic deletion of CD18, the  subunit of 2 integrins, using CRISPR/Cas9 technology. Whereas total neutrophil numbers were unaffected in the absence of CD18, neutrophil trafficking as well as wound healing were significantly impaired in CD18 knock-out zebrafish larvae. By introducing a model for leukocyte adhesion deficiency (LAD) type I in zebrafish, this perspective demonstrates novel findings on the importance of CD18 in this model and discusses current advances as well as potential future directions for studying neutrophil biology in the zebrafish.